Antibody dynamics post-Comirnaty and CoronaVac vaccination in Malaysia - Cheng Siang, Tan; Vaenessa, Noni; Whilemena Upam, Herman Ulok Melina; Ummi Syafqah, Abdorahman; Joseph Niler, Bimbang; Natasya Marliana, Abdul Malik; Mohammad Esa, Hossen; Md Mizanur, Rahman; Lela, Suut; Asri, Said; Claire, Chen; Bego, Sepop; et al. (Springer Nature, 2022)
Several vaccines have been fast-tracked through clinical trials to mitigate the progression of the SARS‑CoV‑2 pandemic. We analyzed sequential blood samples from 314 recipients of Comirnaty and CoronaVac in East Malaysia for the spike-binding IgG (IgG-S), nucleocapsid-binding IgG (IgG-N), spike-binding IgM (IgM-S) and serum vitamin D (VitD). A subset of samples was analyzed for the neutralizing antibodies (Ig-RBD). Results showed that IgG-S due to Comirnaty was significantly higher than CoronaVac. IgM-S was detected in 80.0% Comirnaty and 69.5% CoronaVac recipients, while IgG-N was detected in 58.1% CoronaVac but not in Comirnaty recipients. All IgG-S-positive vaccines possessed detectable Ig-RBD after the second dose but with a weak to moderate correlation. The serum VitD levels did not influence the antibody magnitude in both vaccines. In essence, SARS-CoV-2 vaccination is an IgG-S-dominant event, Comirnaty was more effective than CoronaVac in mounting IgG-S and Ig-RBD responses, independent of the patient’s VitD level.